STATUS HUKUM PERNIKAHAN MUSLIM PASCA PERPINDAHAN KEYAKINAN PERSPEKTIF HUKUM KELUARGA ISLAM DI INDONESIA - Muhazir Muhazir (Universitas Islam Negeri Sumatera Utara, 2021)
Marriage in Indonesia requires the same belief as regulated in the Marriage Law and KHI, this provision is the same as what is regulated in fiqh munakahat. However, sometimes differences in belief occur when the marriage has taken place, this is due to one party changing religions, of course this affects the status of the marriage. The Marriage Law does not regulate the marital status when one party changes religions. However, in Islam the majority of scholars declare to break up marriage. This becomes a problem when faced with social reality. This paper is a literature review with the main data, namely the Marriage Law, KHI and Fiqh munakahat, the approach used is maslahah. The results show that marital status when viewed from the aspect of wasting, the marriage breaks, several empirical studies have shown that marriages based on different beliefs mostly end in disputes and divorce. It's just that the breakup of marriage when you see the divorce system in Indonesia through the Religious Court does not break automatically.